Analysis of the Relationship between Interest and Motivation and Sepak Takraw Achievement of Students at SMAN 1 Montong Gading - Lukman, Lukman; Syarifoedin, Elya Wibawa; Mujriah, Mujriah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to investigate the relationship between students' interest and motivation towards performance in sepak takraw at SMAN 1 Montong Gading, NTB. Sepak takraw is a popular sport in the region, often described as a combination of soccer and volleyball. Psychological factors such as interest and motivation are identified as variables that potentially influence performance in this sport. The research method employed a quantitative descriptive approach with survey and cluster sampling techniques. Data were collected through questionnaires measuring students' levels of interest and motivation towards sepak takraw, as well as their performance in the sport. The results of the analysis indicate a significant correlation between interest (r = 0.416, p < 0.001) and motivation (r = 0.589, p < 0.001) with students' performance. These correlations suggest that higher levels of interest and motivation towards sepak takraw correspond to higher levels of achievement. In conclusion, this study emphasizes the importance of fostering and enhancing students' interest and motivation towards sepak takraw to improve their performance. These findings provide practical implications for developing sports programs in schools aimed at motivating students to achieve better performance through strengthening their interest and motivation